Treatment in patients who are not eligible for intravenous alteplase: MR CLEAN subgroup analysis. Issue 6 (August 2016) - Mulder, Maxim JHL; Berkhemer, Olvert A; Fransen, Puck SS; Beumer, Debbie; van den Berg, Lucie A; Lingsma, Hester F; Roos, Yvo BWEM; van Oostenbrugge, Robert J; van Zwam, Wim H; Majoie, Charles BLM; van der Lugt, Aad; Dippel, Diederik WJ; et al.
Background and purpose: Patients with acute ischemic stroke due to intracranial large vessel occlusion benefit from intra-arterial therapy. Uncertainty exists about the effect of intra-arterial therapy in patients with contraindications for treatment with intravenous alteplase treatment. Our aim was to describe the clinical characteristics of this subgroup of patients and whether intra-arterial therapy is as safe and effective as it is after intravenous alteplase treatment. Methods: All 500 MR CLEAN patients were included and we distinguished between patients who were and were not treated with intravenous alteplase treatment. We estimated the effect of intra-arterial therapy on the shift on the modified Rankin Scale score with ordinal logistic regression analysis and tested for interaction of intravenous alteplase treatment with intra-arterial therapy on outcome. Furthermore, safety parameters and serious adverse events were analyzed. Results: Fifty-five patients (11%) were not treated with intravenous alteplase treatment, mostly because of prolonged coagulation time tests or recent surgery. These patients were older and more often had atrial fibrillation or other vascular comorbidity. There was no interaction between intravenous alteplase treatment and intervention effect ( p  =   0.927). Intra-arterial therapy effect size in patients without intravenous alteplase treatment was 2.06 [95% CI: 0.69–6.13] and in patients with intravenous alteplase treatment 1.71 [95% CI: 1.22–2.40]. There were no safety issues. Conclusions: For patients with acute ischemic anterior circulation stroke caused by intracranial large vessel occlusion, who have contraindications for intravenous alteplase, intra-arterial treatment is not less effective or less safe than in patients who receive the treatment after intravenous alteplase. Clinical trial registration: Clinical trial registration-URL:http://www.trialregister.nl . Unique identifier: (NTR)1804. Clinical trial registration-URL:http://www.controlled-trials.com . Unique identifier: ISRCTN10888758.